Organizational Factors and Individual Factors on the Compliance Level of Nurses and Midwives in Observing Phlebitis - Siti Hunainah; Dewi Kusumawati; Djazuly Chalidyanto; Raissa Manika Purwaningtias (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
This study aimed to analyze the effect of organizational and individual factors on the level of compliance of nurses and midwives in phlebitis observation. This research is an observational analytic study with a cross-sectional design. Respondents of this study were nurses and midwives (n =48) at Inpatient Installation. Data were obtained from questionnaires and secondary data from the IV Usage Surveillance form. The results showed that policy, guidelines, knowledge, and motivation had a positive effect. In contrast, aspects of standard operating procedures and attitudes had an inverse effect on the compliance of nurses and midwives in observing phlebitis. Some nurses and midwives have the weak motivation and the assessment of nurses and midwives that phlebitis observation activities are not supported by the existence of standard operating procedures related to identifying phlebitis signs/scales. The conclusion of this study is the need for an organizational approach to motivate nurses and midwives and provide clear standard operating procedures so that they can change attitudes to become more obedient.